2010
DOI: 10.1002/jmv.21881
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term serological follow‐up of blood donors with an HTLV‐Indeterminate Western Blot: Antibody Profile of Seroconverters and Individuals With False Reactions

Abstract: The high proportion of indeterminate results of the screening test for human T-lymphotropic virus (HTLV) infection has been a challenge worldwide. In this study, 60 persons with seroindeterminate results for HTLV were followed until their serological status was defined. At least two independent serological tests (EIA and WB) from sequential samples were performed at an average interval of 4.4 years, totaling 141 serum samples tested. Seroconversion occurred in 12 individuals (reactive by EIA, positive by WB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
3
24
2
3
Order By: Relevance
“…Thus, there is no evidence that it could be linked to an HTLV-1 seroconversion. This is also strengthened by the fact that during seroconversion following HTLV-1 primary infection, the occurrence of reactivity to p28 is always preceded by the occurrence of p19 and p24 reactivity (17,45,46). Lastly, it is also worth noting that analyses of large series of HTLV WB, performed more than 10/15 years ago in our laboratory, on a series of plasma samples mostly from Cameroon but also, to a lesser extent, from Central African Republic (RCA) and Zaire (now DRC), indicated at that time the presence of such a pattern in a significant percentage of the tested samples (A. Gessain, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, there is no evidence that it could be linked to an HTLV-1 seroconversion. This is also strengthened by the fact that during seroconversion following HTLV-1 primary infection, the occurrence of reactivity to p28 is always preceded by the occurrence of p19 and p24 reactivity (17,45,46). Lastly, it is also worth noting that analyses of large series of HTLV WB, performed more than 10/15 years ago in our laboratory, on a series of plasma samples mostly from Cameroon but also, to a lesser extent, from Central African Republic (RCA) and Zaire (now DRC), indicated at that time the presence of such a pattern in a significant percentage of the tested samples (A. Gessain, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…HTLV indeterminate serologies observed using Western blotting comprise a large variety of patterns, ranging from unique and faint bands (mainly p19 or p24) to complex patterns exhibiting multiple clear bands (44,46,74). We have previously identified and characterized a frequent pattern that we named HGIP, for HTLV Gag indeterminate pattern (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent occurrence of the indeterminate pattern in WB makes it difficult to diagnose the infection correctly. Causes of these indeterminate results have been reported to be cross-reactivity with Plasmodium falciparum infection (13)(14)(15), infection with HTLV-3 and HTLV-4 (16,17), and delayed seroconversion with low antibody titers (18)(19)(20)(21)(22). In those with WBindeterminate samples, the indeterminate result is sometimes sustained for a long time (18,19,23).…”
mentioning
confidence: 99%
“…Causes of these indeterminate results have been reported to be cross-reactivity with Plasmodium falciparum infection (13)(14)(15), infection with HTLV-3 and HTLV-4 (16,17), and delayed seroconversion with low antibody titers (18)(19)(20)(21)(22). In those with WBindeterminate samples, the indeterminate result is sometimes sustained for a long time (18,19,23). Nevertheless, it has been reported that a significant portion of HTLV-1 WB-indeterminate samples are positive for provirus by DNA testing, i.e., 12.5% of WB-indeterminate blood donors in Iran, 9.2% in Brazil, 14.7% (5 of 34) in Argentina, and 42% of patients with neurologic symptoms and 44% of blood donors in the United States (19,(24)(25)(26)(27).…”
mentioning
confidence: 99%